Manipulative Behaviour of the Main Character in “The Orphan” Movie (2009) - Martin; Robby Satria (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study examines the manipulative behavior of the main character, Esther, in the film “The Orphan” (2009) through Sigmund Freud’s psychoanalytic perspective. Manipulation is understood not merely as intentional deception but as the manifestation of unconscious psychological conflicts shaped by trauma and unmet emotional needs. This research aims to identify the forms of manipulation exhibited by Esther and to analyze the psychological motivations underlying her behavior using Freud’s concepts of the Id, Ego, Superego, and defense mechanisms. Employing a descriptive qualitative method, the primary data of this study consist of scenes, dialogues, and visual expressions taken from “The Orphan “(2009). The data were collected through repeated observation and documentation of scenes that depict Esther’s manipulative actions, emotional responses, and interactions with other characters. The analysis was conducted by identifying instances of manipulation, classifying them based on psychoanalytic concepts, and interpreting their psychological meanings in relation to Freud’s theory. The findings are presented descriptively and analytically, supported by selected dialogues and scene descriptions to strengthen the interpretation. The analysis reveals that Esther’s manipulative behavior is driven by the dominance of the Id, weak Ego control, and an underdeveloped Superego, combined with unresolved childhood trauma and fear of abandonment. These internal conflicts lead her to employ deception, emotional manipulation, and aggression as strategies to gain control over others. This study demonstrates the relevance of Freud’s psychoanalytic theory in understanding deviant personality structures in film narratives and contributes to literary and film studies by highlighting the psychological depth of character construction.